Evolusi dan Adaptasi Gerakan Kebangsaan Orang Papua: dari Nasionalisme ke Etnonasionalisme - Hanita, Margaretha (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2019)
Papuan ethnonationalism is the oldest Papuan nationalist movement that arose when outsiders began arriving in Papua with the intention to control the region, since the arrival of Protestant and Catholic missionaries, and the presence of Dutch, Japanese, and Indonesian Indies. Five roots have fostered Papuan ethnonationalism that has evolved to the present: the roots of the Melanesian race, the roots of local religions, the roots of indigenous ties, the roots of the formation of government and political elites in the Dutch East Indies era, and the roots of Feelings of being deprived/uprooted from their land economic exploitation. Papuan ethnonationalism was transformed into Papuan Nationalism which was formed by the Dutch East Indies Government was intended so that West Papua would not become part of the Republic of Indonesia and become an independent state in the process of decolonization carried out by the Dutch in West Papua. But after Indonesia succeeded in taking over West Papua, Papuan Nationalism was transformed back into Ethnonationalism, the symptoms of which have strengthened in the last two decades. This symptom of ethnonationalism strengthens the resilience of the Papua independence movement on the one hand and weakens Indonesia’s national resilience on the other. Papuan ethnonationalism is identical with theories about ethnonationalism and the characteristics of Kurdish and Tamil ethnonationalism.